Impact of After-Sales Service on Customers’ Retention of Mobile Telecommunications in Nigeria - Fasanmi Olumuyiwa Oladapo (Indonesian Journal Of Business And Economics, 2020)
The idea of after-sales services has been adopted globally to provide the consumers after the product or services rendered. The study explored the impact of after-sales services on customers’ retention of mobile telecommunication in Nigeria. Survey research was adopted, and the aim of using this design is premised on the fact that the study relied on obtaining information from the field using a questionnaire. The population consist of all the subscribers of MTN, Globacom, Airtel and 9mobile. Four hundred seventy-two (472) subscribers of mobile networks were proportionally drawn from the NCC website. Subsequently, a simple random sampling technique was used to select the respondents from each of the mobile networks. Data collected were analysed using an application of simple percentage method in computer software packages (SPSS), and the regression analysis adopted by the testing of a reported hypothesis. The regression of [t-statistics] value of .01 and [2.63] demonstrates that the relationship between after-sale service and retention of customers is essential because the alpha level of 0.05 is higher than the p-value. Hence, the assumption is that growth in after-sales activities is a significant contributor to customer retention. Management should pay attention to the employee position to the quality of after-sales service, which results in future procurement and further recommendations.